Technographic segmentation using neural network at the Rainforest World Music Festival / Nur Balqish Hassan ... [et al.] - Hassan, Nur Balqish; Hashim, Noor Hazarina; Bakhary, Norhisham; Padil, Khairul H. (Universiti Teknologi Mara Selangor, 2019)
Market segmentation is a marketing strategy practice that divides consumers into groups with varying needs and interests. This helps marketers to understand the subgroups' needs and to tailor their marketing efforts and product offerings to meet those needs. Event marketers are no exception. Although the most frequently used technique in identifying market segment, cluster analysis, yields unstable results and cannot handle large data sets, neural networks can overcome these problems. This study proposes the development of technographic segmentation of visitors attending a music festival based on their smartphone usage and a combination of psychographic and behavioral factors. This system classifies consumers based on motivations, use patterns, and attitudes towards technology. It uses cluster analysis to identify segments, and to demonstrate the applicability of using neural network for segmentation process.